2015
DOI: 10.17245/jdapm.2015.15.2.69
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of an elevated concentration of lidocaine HCl in impacted lower third molar surgery

Abstract: BackgroundThere have been few studies on the effect of an elevated concentration of lidocaine hydrochloride in the surgical removal of an impacted lower third molar. This study aimed to examine the efficacy of 4% lidocaine along with 1:100,000 epinephrine compared to 2% lidocaine along with 1:100,000 epinephrine as inferior alveolar nerve block for the removal of an impacted lower third molar.MethodsThis single-blind study involved 31 healthy patients (mean age: 23 y; range: 19-33 y) with symmetrically impacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In terms of the heterogeneity of each outcome, this can be explained by the formulation and dosage of anesthetic solution. Ping et al 33 suggested that IANB using 4L100 was more effective than that using 2L100, and epinephrine is an excellent vasoconstrictor with varying degrees of efficiency, depending on the concentration of epinephrine added to lidocaine. 34 Three studies reported that the dosage of anesthesia could affect the efficiency of anesthesia, in that a greater volume could increase anesthetic efficiency.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…In terms of the heterogeneity of each outcome, this can be explained by the formulation and dosage of anesthetic solution. Ping et al 33 suggested that IANB using 4L100 was more effective than that using 2L100, and epinephrine is an excellent vasoconstrictor with varying degrees of efficiency, depending on the concentration of epinephrine added to lidocaine. 34 Three studies reported that the dosage of anesthesia could affect the efficiency of anesthesia, in that a greater volume could increase anesthetic efficiency.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…A previously published study used a 3-4 week interval between the first and second surgeries for patients with bilateral lower third molar surgery [ 3 4 12 ]. Therefore, we chose a 3-week interval between the surgeries in this study so that postoperative sequelae of the local anesthetic injection, such as pain and numbness, were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In many previous studies, researchers have tried to manipulate the physical and chemical properties of local anesthetics to improve their effectiveness when used for the inferior alveolar nerve (IAN) block. Researchers have compared different types and volumes [ 2 3 4 ] of local anesthetics and have modified the concentration of the buffering agent in the local anesthetic cartridge. Previous studies have commonly reported on the onset, duration of action, and success rate of pulpal anesthesia observed with the different methods [ 5 6 7 8 9 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 27-gauge needle (30 mm) and self-aspirating syringes with a local anesthetic solution (4% articaine with adrenaline 1:100,000 [1 cartridge = 1.7 ml]) were used. The standard IANB technique was followed [ 3 4 5 ]. The anesthetic was injected into the pterygomandibular space, while the axis of the syringe barrel was parallel and was placed on the occlusal surfaces of the mandibular teeth.…”
Section: Methodsmentioning
confidence: 99%